IMPLEMENTASI STANDAR OPERASIONAL PROSEDUR PENGURUSAN STNK KENDARAAN DINAS BIDANG PERLENGKAPAN DAN PELAYANAN PENGADAAN PEMKOT MEDAN - Yuna Febriani Dalimunthe; Mardiansyah Mardiansyah (STKIP PGRI TULUNGAGUNG, 2022)
Standard Operating Procedures (SOP) for managing vehicle registrations for government service vehicles in Medan City. STNK is a letter issued by the Indonesian National Police as a proof of registration of a motorized vehicle. In the management and extension of the vehicle registration certificate, which is the responsibility of the field for equipment and procurement, the Medan City Government must comply with the existing SOP. This study aims to determine the implementation of standard operating procedures for managing vehicle registrations for the Medan City Government Service in the field of equipment and procurement services for the Medan City Government. This study uses a qualitative descriptive method to help analyze the data and facts obtained. The data obtained in this study used descriptive analysis which was the result of interviews with informants. Based on the results of data analysis, the implementation of standard operating procedures for obtaining STNK for Medan City government official vehicles in the field of equipment and procurement services runs according to the SOP. The success of the SOP implementation can be seen from the answers of the informants in the research both in terms of Bureaucratic Structure, Communication, Human Resources and Disposition or Attitude.